Transvaginal sonographic cervical length during mid-trimester in predicting preterm labour in asymptomatic singleton pregnancies - Mahammad, Shamshad Begum; Sunkireddy, Nagamani; M., Jayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Worldwide, preterm birth is the main contributor to perinatal mortality and morbidity. Preterm birth causes 50% of long-term morbidity, contributes 75% of neonatal deaths (after accounting for fatal abnormalities), and becomes 85% of newborn deaths. Cervical length measurement has been linked to predicting the preterm labour in mid-trimester by various studies. Methods: This study was carried out to evaluate the strength of cervical length as a predictive factor for pre-term labour. This is a prospective observational study conducted at MIMS, Vizianagaram on 100 antenatal mothers. The cervical length is measured by transvaginal ultrasound. If the length was <25 mm, then the patients were advised a second scan during 28th week and follow-up was done till delivery. Results: Out of the 100 patients, 21 were multigravida, whereas 79 were primigravida. 20 had pre-term delivery and 80 had term delivery. The mean age of the population was 25.2±4.5 years. 40% of cases with cervical length <25 mm had pre-term delivery, as compared to 33.33% in patients with cervical length 26-30 mm, 13.63% in 31-35 mm, 5.88% in 36-40 mm and 16.66% in patients with cervical length >40 mm. The p value<0.05. Area under ROC curve is 0.79. Sensitivity is 60%, specificity is 8.75%, positive predictive value is 57.14%, negative predictive value is 89.87%. Conclusions: Transvaginal sonography is a reliable diagnostic test in mid-trimester in predicting pre-term delivery in singleton pregnancy.